Myelotoxic effects of cholaramphenicol and its metabolites - Ahmet Levent Baş (Eurasian Journal of Veterinary Sciences)
Chloramphenicol has a broad spectrum of activity against both gram negative and gram positive bacteria, richetsia, and psittacozis-lymphogranuloma group. The most important unwanted eflect of chloramphenicol is depression of the bone-marrow resulting in pancytopenia- an effect which may occur even with very low doses in some indivudiats.Within the Turkey the drug is approved for use only in non-food producing animals: it is illegal to use the drug in food animals. Prohibition of chloramphenicol for use in food animals is based in the tendency of chloramphenicol or its metabolites to produce aplastic anemia in certain susceptibie people. In this review, the myelotoxic effects of chloramphenicol and its metabolites are summarized.